Lesson From Other Discipline’s Decision in Managing Giant Haemangioma Of The Hemithorax : Case Report - Djaprie, Shelly M; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
The management of the giant and moderate size infantile haemangiomas are challenging problems, especially in health systems with limited resources in developing countries. The aim of presenting this case is to take a lesson from another discipline’s decision in managing haemangioma. The author provide information based on clinical examination and surgical records of the patient with giant hemangioma which was consulted to plastic surgery team. A four month year old boy was consulted by pediatric surgery team with a giant size haemangioma on the right hemithorax.The treatment option for each haemangioma are different based on the case itself. Especially for this case, it seems better to be treated conservatively due to several reason, such as the phase of hemangioma, the location of the mass, the size, the donor morbidity. Early surgical excision of a moderate size infantile haemangioma may be justified especially when there is dificulty of follow-up. This approach will prevent growth deformation, impact on nearby vital organs and psychological problems.